Composition and function of P bodies in Arabidopsis thaliana - Maldonado-Bonilla, Luis D. (Frontiers in Plant Science, 2014)
mRNA accumulation is tightly regulated by diverse molecular pathways. The identification and characterization of enzymes and regulatory proteins involved in controlling the fate of mRNA offers the possibility to broaden our understanding of posttranscriptional gene regulation. Processing bodies (P bodies, PB) are cytoplasmic protein complexes involved in degradation and translational arrest of mRNA. Composition and dynamics of these subcellular structures have been studied in animal systems, yeasts and in the model plant Arabidopsis. Their assembly implies the aggregation of specific factors related to decapping, deadenylation and exoribonucleases that operate synchronously to regulate certain mRNA targets during development and adaptation to stress. Although the general function of PB along with the flow of genetic information is understood, several questions still remain open. This review summarizes data on the composition, potential molecular roles, and biological significance of PB and potentially related proteins in Arabidopsis.